National income and expenditure - Richard (London : Bowes & Bowes (Publishers) Ltd, 1961)
This book is about the concepts of national income and expenditure and how these concepts fit into an accounting structure of the national economy
Includes bibliographical references
osa; 03/12/19
Loans
Keywords: Giovanna Stone; National income; Consumer; National income - Great Britain